2016
DOI: 10.1089/end.2015.0768
|View full text |Cite
|
Sign up to set email alerts
|

Thulium Laser in the Upper Urinary Tract: Does the Heat Generation in the Irrigation Fluid Pose a Risk? Evidence from an In Vivo Experimental Study

Abstract: The use of Tm:YAG in continuous mode with power settings up to 40 W and flow rates similar to those used in the clinical practice seemed to result in temperature increases in the irrigation fluid, which do not represent a risk for the renal tissue during the UT endoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…There is mounting evidence concerning the potentially harming thermal side effects of Ho:YAG and Tm:YAG lasers in in vitro investigations, which leads to the question whether there might be a relevant temperature increase of the irrigation fluid during Tm:YAG laser-based procedures [11][12][13][14]. The present work´s objective was to investigate the thermal effect of a 120 W Tm:YAG laser in a standardized in vitro prostate simulation setting on the surrounding irrigation fluid (urethra), the prostate parenchyma and deeper anatomical structures like the neurovascular bundles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is mounting evidence concerning the potentially harming thermal side effects of Ho:YAG and Tm:YAG lasers in in vitro investigations, which leads to the question whether there might be a relevant temperature increase of the irrigation fluid during Tm:YAG laser-based procedures [11][12][13][14]. The present work´s objective was to investigate the thermal effect of a 120 W Tm:YAG laser in a standardized in vitro prostate simulation setting on the surrounding irrigation fluid (urethra), the prostate parenchyma and deeper anatomical structures like the neurovascular bundles.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological mechanisms of atypical postoperative complications after transurethral LUTS treatment and transient urge incontinence-independently from the source of energy-are not entirely understood. In several recent in vitro and animal studies, significant temperature increases of the irrigation fluid were confirmed in both Ho:YAG-and Tm:YAG models [11][12][13][14][15][16]. A theoretically available laser power up to 200 W in ThuVA(R)P, besides a high tissue ablation efficiency, might bear a high risk for the development of significant temperature increases of the surrounding irrigation fluid and tissue.…”
Section: Introductionmentioning
confidence: 90%
“…Specifically, thulium laser characteristics allow to obtain an optimal coagulative effect with a shallow penetration in the tissues. [21][22][23][24] Conclusion: Thulium laser can effectively coagulate endometriotic bleeding spots in residual ureteral tissue and could be used to control ureteral endometriosis with an endoscopic approach. However, a longer follow-up is needed.…”
Section: Thulium Laser Coagulation Of Residual Ureteral Endometriosismentioning
confidence: 99%
“…3 Thulium laser lithotripsy has recently undergone further improvements, especially Thulium fiber lasers (TFL), and has been extensively investigated in terms of dusting/ fragmenting efficiency, stone ablation threshold/rates, gas bubble formation, and collateral damage assessment. [4][5][6][7][8][9][10][11][12][13][14][15] Taratkin and colleagues showed that TFL and Ho:YAG have a similar temperature behavior at identical power settings. 15 Dornier MedTech Laser GmbH (Wessling, Germany) provided an evaluation model of a novel Thulium pulsed solid-state laser that should not be confused with a TFL.…”
Section: Introductionmentioning
confidence: 99%